2015
DOI: 10.1177/0038038515591945
|View full text |Cite
|
Sign up to set email alerts
|

Seeing the Baby, Doing Family: Commercial Ultrasound as Family Practice?

Abstract: A note on versions:The version presented here may differ from the published version or, version of record, if you wish to cite this item you are advised to consult the publisher's version. Please see the 'permanent WRAP URL' above for details on accessing the published version and note that access may require a subscription.For more information, please contact the WRAP Team at: wrap@warwick.ac.uk 1 Seeing the baby, doing family: commercial ultrasound as family practice?ABSTRACT Medical sociologists and anthrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…For more information on methodology and data analysis for both studies, see (Roberts et al . , ; Thomas ).…”
Section: Research Contexts: Two Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…For more information on methodology and data analysis for both studies, see (Roberts et al . , ; Thomas ).…”
Section: Research Contexts: Two Studiesmentioning
confidence: 99%
“…Ethical approval was granted by NHS and university research ethics committees for both studies. For more information on methodology and data analysis for both studies, see (Roberts et al 2015a(Roberts et al , 2015bThomas 2017).…”
Section: Research Contexts: Two Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Smart's ‘connectedness thesis' (2007: 189) has been used to explore family experiences of living with life‐threatening illness (Ellis ), narratives of household work practices (Kettle ) and family use of commercial ultrasound (Roberts et al . ). These authors have shown how the concepts of memory, biography, embeddedness, relationism and the imaginary (Smart ) can be used to theorise how family is created through social action.…”
Section: Introductionmentioning
confidence: 97%
“…Building on this, we follow Smart who argues for a greater focus on thinking, feeling and imagining, the interior processes that are entwined with the practices that constitute family (and the non-familial relationships that are part of our personal lives). 1 Smart's 'connectedness thesis' (2007: 189) has been used to explore family experiences of living with life-threatening illness (Ellis 2013), narratives of household work practices (Kettle 2016) and family use of commercial ultrasound (Roberts et al 2017). These authors have shown how the concepts of memory, biography, embeddedness, relationism and the imaginary (Smart 2007) can be used to theorise how family is created through social action.…”
Section: Introductionmentioning
confidence: 99%